Bimbingan dan Konseling Pada Lembaga Pendidikan Anak Usia Dini - Edris Zamroni (Universitas Mathla'ul Anwar Banten, 2018)
GUIDANCE AND COUNSELING IN EARLY CHILDHOOD EDUCATION. Implementation of guidance and counseling in early childhood education institutions is a necessity. The juridical strengthening of guidance and counseling as part of education that can also touch early childhood education institutions starting from the issuance of Law no. 20 of 2003 on the National Education System, followed by various derivatives of other regulations such as Government Regulation No. 19/2005 on National Education Standards, Government Regulation Number 74 Year 2008 on Teachers and Education Personnel, Permendiknas Number 27 Year 2008 to Permendikbud Number 111 Year 2014 on Guidance and Counseling on Primary and Secondary Education. Scientifically guidance and counseling study about human development holistically so relevant to the main purpose of early childhood education with the orientation of child development facilitation. This paper examines the relevance of scientific guidance and counseling to be implemented in early childhood education institutions and the legal basis that reinforces the practice.